The possible role of propofol in drug-induced torsades de pointes: A real-world single-center analysis. (1st April 2017) - Abrich, Victor A.; Ramakrishna, Harish; Mehta, Arjun; Mookadam, Farouk; Srivathsan, Komandoor
Abstract: Background: Torsades de pointes (TdP) is a polymorphic ventricular tachycardia associated with QT prolongation. Propofol is a sedative-anesthetic with proarrhythmic effects on cardiac myocytes. We performed a retrospective study to determine the incidence of TdP following propofol exposure at Mayo Clinic (Rochester, MN) from 08/11/1998–11/20/2015. Methods: We queried our database using key search terms to identify patients exposed to propofol who developed TdP perioperatively or during non-surgical sedation. QT intervals were obtained from electrocardiograms (ECGs) performed before propofol exposure and after documented TdP and were corrected using Fridericia and Framingham methods. T wave peak-to-end (Tp-e)/QT ratios were also calculated. Results: A total of 628, 784 patients received propofol over 17.3 years. Of these patients, 21 developed TdP (12, postoperatively; 3, intraoperatively; 6, during sedation). There were 17 patients who were exposed to at least one factor associated with QT-prolongation, including QT-prolonging medications in 8 patients, heart rate < 60 beats per minute in 8 patients, potassium < 3.5 mmol/L in 4 patients, magnesium < 1.8 mg/dL in 2 patients, and subarachnoid hemorrhage in 2 patients. The number of patients with QTc > 500 ms using Fridericia correction was significantly higher from baseline following exposure to propofol (1 patient vs 6 patients, P = 0.04); however no significant difference was observed with Framingham correction. Conclusion: In our study, TdP after propofol administration occurred with an annual incidence of 1.93 per million and was often associated with other risk factors. Nevertheless, propofol should be administered with caution in patients at risk of developing TdP.